Blocking Histamine H1 Improves Learning and Mnemonic Dysfunction in Mice With Social Isolation Plus Repeated Methamphetamine Injection - Feiyong Jia; Jalal Izadi Mobarakeh; Hongmei Dai; Motohisa Kato; Ajing Xu; Tomohiro Okuda; Eiko Sakurai; Nobuyuki Okamura; Kazuhiro Takahashi; Kazuhiko Yanai (Elsevier, 2008)
The aim of this study was to investigate the effects of histamine H1 and H3 antagonists on learning and mnemonic dysfunction in mice. Two H1 antagonists, pyrilamine and clozapine, and the prototypic H3 antagonist thioperamide were used to study the role of histamine in mice with social isolation and repeated methamphetamine administration. Mice with social isolation and repeated methamphetamine administration showed significant disruption of prepulse inhibition as compared to both the socially-housed mice and isolation-housing mice. Furthermore, social isolation and repeated methamphetamine administration caused significant learning and mnemonic dysfunctions. Treatment with clozapine improved learning and mnemonic ability in all of the tasks. Pyrilamine treatment ameliorated performance in all the tests examined except for the passive avoidance test. Thioperamide, however, did not change the learning and mnemonic ability. Donepezil, an acetylcholinesterase inhibitor, reversed the learning and mnemonic dysfunction in all four tasks. The present study has shown that blockade of histamine H1 receptor improved the learning and mnemonic ability in mice, raising the possibility that treatment with clozapine or pyrilamine may improve learning and mnemonic performance in certain patients with psychiatric diseases such as schizophrenic patients with cognitive dysfunction. Keywords:: memory, social isolation, histamine, H1 receptor, methamphetamine